The Implementation of Flipped Classroom Learning Model Using Moodle To Increase Students’ Higher Order Thinking Skills - Huzaima Mas'ud; Herman Dwi Surjono (Journal of Educational Science and Technology (EST), 2018)
This study aims to reveal the differences in the learning achievement based on higher order thinking skills of the students using flipped classroom learning model with moodle media on simulation and digital communication subjects and that of those using the conventional learning model with printed book media. This research was a quasi experiment in the form of pre-test and post-test group. The population was all students of class X TKJ SMK Negeri 3 Kab.Pinrang, totaling 62 students. The sample was established using intact group technique based on the existing class. The data were collected through a test to measure student learning achievement based on higher order thinking skills, a questionnaire with Likert scale, and documentation. Measurements were based on students’ learning achievement scores and responses to the flipped classroom learning model. The data were analyzed using the descriptive statistics and inferential statistics. The results shows that, there were differences in students’ learning outcomes based on higher order thinking skills using flipped classroom learning model with moodle media on simulation and digital communication subjects compared with learning outcome using conventional learning model / lecture with printed book media, namely the mean of experimental class groups 30.41 while the control class group 27.70 from the highest score 35 in the experimental class and 33 in the control class and proved by results of hypothesis testing with a probability value of 0.032 < 0.05 H1 accepted.